The Croc Takes the Cake - La Rose, Melinda; Batson, Alan; Disney Enterprises (1996- ) (New York : Disney Press, 2012)
Jake, Izzy, and Cubby make Captain Hook a birthday cake for his birthday.
At head of title: Disney Jake and the Never Land Pirates.
"Disney Junior"--Cover.
Accelerated Reader AR
Keywords: Pirates -- Juvenile fiction; Birthday cakes -- Juvenile fiction